The meaning of the snake in the ancient Greek world - Rodriguez-Perez, D (MDPI, 2020)
Despite playing no meaningful practical role in the lives of the ancient Greeks, snakes are ubiquitous in their material culture and literary accounts, in particular in narratives which emphasise their role of guardian animals. This paper will mainly utilise vase paintings as a source of information, with literary references for further elucidation, to explain why the snake had such a prominent role and thus clarify its meaning within the cultural context of Archaic and Classical Greece, with a particular focus on Athens. Previous scholarship has tended to focus on dualistic opposites, such as life/death, nature/culture, and creation/destruction. This paper argues instead that ancient Greeks perceived the existence of a special primordial force living within, emanating from, or symbolised by the snake; a force which is not more—and not less—than pure life, with all its paradoxes and complexities. Thus, the snake reveals itself as an excellent medium for accessing Greek ideas about the divine, anthropomorphism, and ancestry, the relationship between humans, nature and the supernatural, and the negotiation of the inevitable dichotomy of old and new.